Analisis Usaha Penangkapan Rajungan Dengan Bubu Lipat di Desa Waruduwur Kabupaten Cirebon - Dedi Supriadi; Yuyun Yuyun; Restu Widayaka (Barakuda'45, 2020)
This study aims to determine the level of income of swimming crab catches and other side catches carried out by portable traps fishermen in Waruduwur Village, Cirebon Regency, as well as to know the factors of production costs that affect the acquisition of production volume of portable traps catches. This research uses methodology descriptively with surveys. Respondents were as many as 10 (ten) bubu folding fishermen who used boats with a size < 5 GT. The average income level of swimming crabs fishing business for ten respondents of portable traps fishermen folded in ten arrest trips amounting to Rp. 4,354,420.00 with an average operating cost value of Rp 2,302,110.00 and an average profit value of Rp 2,052,310.00. The amount of average value of income does not guarantee the amount of profit achieved, given the difference in the amount of operating costs at sea. Factors of production costs that affect the acquisition of production volumes of swimming crabs catches are oil, diesel (BBM) and Supplies. With details of the percentage of oil 3.72 % of Rp 82,500.00, then diesel 26.39% amounted to Rp 594,000.00, and supplies of 69.89% was Rp.1,625,610.00, so the most dominant production costs influenced the acquisition of the volume of swimming crabs catches in a row were marine supplies, diesel and oil.